Optimisation of calcinothermic reduction for metallic dysprosium preparation - Nguyen Trong Hung; Nguyen Thanh Thuy; Le Ba Thuan (Vietnam Journal of Science, Technology and Engineering, 2024)
This research focuses on optimising the process of preparing metallic dysprosium through calcinothermic reduction. The study employed response surface methodology (RSM) based on a central composite face-centred (CCF) design to model the interactive effects of three independent variables: reduction temperature, Ca/DyF3 molar ratio, and reduction time, on the dependent response, which was the reduction yield. Initially, experiments were conducted to determine the experimental matrix or planning region. Subsequently, experimental studies were carried out within this matrix to develop a quadratic response surface methodology - central composite face (RSM-CCF) model for the calcinothermic reduction of DyF3 using MODDE 5.0 software. The resulting model demonstrated good agreement between calculated and actual data, establishing a reliable framework for the calcinothermic reduction process. Further analysis involved assessing the contributions of the model’s coefficients to the dependent response to optimise the process. The findings indicate that reduction temperature plays a significant role in governing the calcinothermic reduction. The optimal parameters for the calcinothermic reduction of DyF3 were identified as a reduction temperature of 1450-1460°C, a reduction time of 50 minutes, and a Ca/DyF3 molar ratio of 2.15. Under these conditions, the maximum reduction yield achieved was 85.7%.